The relationships between cage floor preferences and performance in broiler chickens - Idrus, Zulkifli; A., Siti Khatijah (Asian-Australasian Association of Animal Production Societies, 1998)
Two experiments were conducted with broiler chickens to determine cage floor preferences, the strength of preference for a particular floor type and to evaluate the effect of rearing broilers on the preferred cage floor on productivity. In experiment 1, chicks when offered free access to either wire (WF) or plastic (PF) mesh flooring, preferred the former. However, when the perferred floor type (WF) was illuminated at 800 lux, birds spent longer time on PF. Also provision of incandescent lamps at PF resulted in broilers spending significantly longer period on WF. In experiment 2, while floor type had no effect on growth of female chicks throughout the duration of study, male chicks grown on PF were heavier than their WF counterparts on Days 21, 28, 35 and 42. Neither livability, nor incidence of breast blisters and leg deformities was affected by floor type.